First record of the invasive red alga Polysiphonia morrowii Harvey (Rhodomelaceae, Rhodophyta) on the Patagonian shores of the Southwestern Atlantic - Raffo, María Paula (2014)
Seaweed invasions are recognized as one of the major threats to biological diversity and coastal resources. Nevertheless, the number of introduced macroalgae has been underestimated due to the increasing number of cryptic invasions. Polysiphonia morrowii is native to the North Pacific and several cryptic introductions of this species have been reported over the past decade. In this study, we recorded the presence of the invasive P. morrowii in the Southwestern Atlantic (Patagonia Argentina) using a morphological and molecular approach for the identification at species level. Polysiphonia morrowii specimens from Argentina showed no morphological differences from members of invasive populations in France. We found two different haplotypes, suggesting that P. morrowii was probably introduced into this area by multiple introduction events. The increasing number of shipping and aquaculture activities worldwide and the ability of this species to be a successful invader suggest that P. morrowii is likely to be a cosmopolitan invasive species and that further management planning is required for its early detection and control.